Isolation and Characterization of Avian Influenza Virus Based on Macroscopic Examination of Native Chicken Embryo - Fakhrurrazi Fakhrurrazi; Hamdani Budiman (Universitas Syiah Kuala, 2009)
The aim of this research was to isolate and characterize the virus based on macroscopic examination of native chickens embryo infected with the AI virus. This research used 10 infected native chickens from Ateuk Pahlawan and Doi villages. All chickens were examined to identify the present of AI using rapid test and in ovo virus propagation. Rapid test showed 7 chickens from Ateuk Pahlawan villageand 5 chickens from Doi village were AI positive. Propagation of the viruses in 11 days old chicken embryo in ovo showed that embryo died 5 days post inoculated whereas macroscopic examination showed dwarfed embryo, hemorrhagic, and loss of feather.